2005
DOI: 10.1074/jbc.m509050200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Mutagenesis and Substituted Cysteine Accessibility Analysis of Transmembrane Segment 4 of the Glut1 Glucose Transporter

Abstract: A low resolution model has been proposed for the exofacial conformation of the Glut1 glucose transporter in which eight transmembrane segments form an inner helical bundle stabilized by four outer helices. The role of transmembrane segment 4, predicted to be an inner helix in this structural model, was investigated by cysteinescanning mutagenesis in conjunction with the substituted cysteine accessibility method using the membrane-impermeant, sulfhydrylspecific reagent, p-chloromercuribenzenesulfonate (pCMBS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Note that the orientations of helices 4 and 12 are arbitrary because of the absence of reactivity in the former case or lack of periodicity in pCMBS sensitivity in the latter. Also, although helix 4 is shown as an inner helix in this diagram, its lack of pCMBS sensitivity suggests that its exoplasmic end may lie outside of the inner bundle in the exofacial orientation (25). It should also be emphasized that it is uncertain as to whether the structural and biophysical properties of Glut proteins are identical in Xenopus oocytes and in native mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the orientations of helices 4 and 12 are arbitrary because of the absence of reactivity in the former case or lack of periodicity in pCMBS sensitivity in the latter. Also, although helix 4 is shown as an inner helix in this diagram, its lack of pCMBS sensitivity suggests that its exoplasmic end may lie outside of the inner bundle in the exofacial orientation (25). It should also be emphasized that it is uncertain as to whether the structural and biophysical properties of Glut proteins are identical in Xenopus oocytes and in native mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Homology modeling of the cytoplasmic conformation of Glut1 based on these structures suggests that helices 1, 2, 4, 5, 7, 8, 10, and 11 comprise an inner bundle of transmembrane helices that form a substrate-binding site near the center of the bilayer, whereas helices 3, 6, 9, and 12 are predicted to encircle this inner helical bundle (24). The available experimental evidence suggests that the exofacial half of helix 4 may not be exposed to the external aqueous compartment in the exofacial configuration (25), although it comprises an inner helix in the endofacial confor-mations of the bacterial transporters. It is thus possible that the cytoplasmic and exoplasmic arrangements of the inner helical bundle of MFS transporters are not identical.…”
mentioning
confidence: 99%
“…45,62,63 Cysteine scanning mutagenesis was subsequently employed to probe which residues lined this proposed central pore. [64][65][66][67][68][69][70][71][72][73][74] The resulting model indicated that TMs 2, 4, 5, 7, 8, 11, and possibly 1 and 10 formed a central aqueous transport channel for glucose, whereas TMs 3, 6, 9, and 12 formed a structural scaffold on the outside of the protein. 70 A possible substrate binding site was also proposed, involving Q161, Q282, and W412.…”
Section: Structure Of Human Glut1mentioning
confidence: 99%
“…SCAM analysis is a well-established methodology to identify amino acid residues of which the side chain is exposed into the ligand-binding site of receptors or the substrate-binding site of transporters (23,24). We have replaced different residues of TMD IV and TMD VIII in Pho84 individually by cysteine using site-directed mutagenesis.…”
mentioning
confidence: 99%